Pemanfaatan Limbah Kina Masa Lampau dan Pengembangannya : Utilization of Quinine Waste in The Past and Its Development - Ria Intani T; Lasmiyati Lasmiyati (JURNAL PANALUNGTIK, 2021)
As of today, quinine plants are still found in the Bukit Unggul Plantation, Bandung Regency, which is part of PT Perkebunan Nusantara VIII. Quinine is processed in the processing plant located in Bukit Unggul. In general, people have known quinine as an anti-malarial drug in which the ingredients were taken from the bark of the quinine tree trunk, afterward it becomes waste. In the past, quinine waste was used as firewood and building material for offices, factories, and homes for plantation worker. In its development, there were those who use quinine waste to make furniture to meet their own needs. The results showed that the previous idea of using quinine waste inspired people in the future to utilize and develop quinine waste into furniture, in a sense of worth-selling furniture. The purpose of this study is to demonstrate the utilization of quinine waste in the past and its development. This is descriptive research with a qualitative approach. The data collection was carried out using interview, observation, and documentation studies. The conclusion of the study is that the discourse about quinine became widespread, not only limited to medicine, but also building materials and crafts.